Climate change impacts and adaptation measures for Quy Nhon city - Van, Tran Thi; Thai, Tran Hong (VNU Journal of Science: Earth and Environmental Sciences; Vol 27 No 2, 2011)
Abstract. In the framework of the program "Asian Cities Climate Change Resilience Network" funded by Rockefeller Foundation, Vietnam Institute of Hydrology, Meteorology and Environment carried out this study with the aim to strongly support the development of action plan to respond to climate change for Quy Nhon city. The study developed climate change (temperature and rainfall) and sea level rise scenarios corresponding to some key emission scenarios, namely A1FI, A2 and B2. Impacts of climate change on main sectors such as water resources, agriculture and tourism were also assessed. These were used as the basis for proposing adaptation measures. Keywords: climate change, adaptation measures, Quy Nhon.